O bebê que não nasceu: stress e coping da equipe de enfermagem que lida com a morte fetal - Cravinho, Camilla Ramos Medalane (2014)
Fetal death from pregnancy loss results in stress for healthcare professionals who need to adopt strategies (coping) to deal with the grief arising from this situation in your work environment. In this sense, the present study investigated how nursing professionals deal with fetal death in the hospital setting based on research and analysis of indicators of stress and coping, besides cognitive and emotional aspects related to the topic. Participants were 36 professional nursing staff of two public hospitals connected to the SUS with 20 participants from Doutor Dorio Silva Hospital , located in Vitoria / ES and 16 from Maternity Hospital of Federal University of Rio de Janeiro / RJ . After signing the Term of Free and Informed Consent, which was approved by the Ethics Committee , participants answered the following instruments : 1 ) Lipp Stress Symptom Inventory; 2) Nurse Stress Inventory 3 ) COPE Inventory ; 4 ) Roadmaps Interviews: a) “Coping Motivational Interview” and b ) "Cognitive and emotional aspects up front fetal death Interview " , both designed specifically for the study , and 5) a general protocol for sample characterization data . The data were processed according to the rules of the scales and through descriptive and correlational statistical analysis; verbal reports obtained in the interviews were processed by the method of Content Analysis. The theoretical referential adopted for analyzing the results was the Motivational Theory of Coping developed by E. Skinner and the Dispositional Approach Coping by C.Carver. It was observed that half of the sample was stressed at Lipp Stress Symptom Inventory; of these, 41,7% was found in the resistance phase with similar incidence of 14 psychological symptoms (44.4%) and physical (44,4%) . By the Nurse Stress Inventory there was a low intensity occupational stress, whose overall average was 2,36. In the assessment of coping by the COPE Inventory was found that the strategies most used by professionals of both institutions were Religiosity (Md = 13,5) followed by positive Reinterpretation and Growth ( Md = 13 ) , Planning ( Md = 12 ) , Active Coping ( Md = 11 ) and Acceptance (Md = 11) . In the analysis of the coping Interview Guide “Coping Motivational” the Negotiation which was the most frequent family (N = 35), followed by the Information Seeking (N = 33) Self-reliance (N = 25 ) and Support Seeking (N = 23). In the “Cognitive and emotional aspects up front of fetal death” interview observed predominance (N = 21) of reports which considered fetal death as a stressor and as an event denied / unwanted (N = 21), associated with feelings of sadness. It is concluded that although fetal death be considered a stressor, professionals, in general, used adaptive strategies to deal with this situation.